Genotypes and phenotypes in children with short stature: clinical indicators of SHOX haploinsufficiency. Issue 5 (20th December 2006) - Rappold, Gudrun; Blum, Werner F; Shavrikova, Elena P; Crowe, Brenda J; Roeth, Ralph; Quigley, Charmian A; Ross, Judith L; Niesler, Beate
Abstract : Background: Short stature affects approximately 2% of children, representing one of the more frequent disorders for which clinical attention is sought during childhood. Despite assumed genetic heterogeneity, mutations or deletions of the short stature homeobox-containing gene ( SHOX ) are found quite frequently in subjects with short stature. Haploinsufficiency of the SHOX gene causes short stature with highly variable clinical severity, ranging from isolated short stature without dysmorphic features to Léri-Weill syndrome, and with no functional copy of the SHOX gene, Langer syndrome. Methods: To characterise the clinical and molecular spectrum of SHOX deficiency in childhood we assessed the association between genotype and phenotype in a large cohort of children of short stature from 14 countries. Results: Screening of 1608 unrelated individuals with sporadic or familial short stature revealed SHOX mutations or deletions in 68 individuals (4.2%): complete deletions in 48 (70.6%), partial deletions in 4 (5.9%) and point mutations in 16 individuals (23.5%). Although mean height standard deviation score (SDS) was not different between participants of short stature with or without identified SHOX gene defects (–2.6 vs –2.6), detailed examination revealed that certain bone deformities and dysmorphic signs, such as short forearm and lower leg, cubitus valgus, Madelung deformity, high-arched palate and muscular hypertrophy, differed markedly between participants with or without SHOX gene defects (p<0.001). Phenotypic data were also compared for 33 children with Turner syndrome in whom haploinsufficiency of SHOX is thought to be responsible for the height deficit. Conclusion: A phenotype scoring system was developed that could assist in identifying the most appropriate subjects for SHOX testing. This study offers a detailed genotype-phenotype analysis in a large cohort of children of short stature, and provides quantitative clinical guidelines for testing of the SHOX gene.